A new species of Arnobia (Orthoptera: Phaneropteridae: Phaneropterinae) from Sakaerat, Thailand - Tan, Ming Kai; Artchawakom, Taksin (Zootaxa, 2014)
From Sakaerat Environmental Research Station, Nakhon Ratchasima, Thailand, one new species of Arnobia (Orthoptera: Phaneropterinae) is described: Arnobia tinae sp. n.